A GRICE'S COOPERATIVE PRINCIPLE ANALYSIS OF A PERSON WITH AUTISTIC SPECTRUM DISORDER (ASD): A Case Study of a 20 year-old Male with ASD in SLBC Sumbersari Bandung - Pamungkas, Mayu (2014)
The present study examines the types of maxims observed by a person with Autistic Spectrum Disorder (ASD), the types of maxims not observed and their non-observance, and factors contributing to the participant in observing and not observing the maxim. The data are in the form recorded observation of conversations with a person with ASD at SLBC Sumber Sari Bandung. The study employs a qualitative design with some measures of descriptive statistics. Grice's Cooperative Principle theory (1975) is applied to analyze the realization of Grice's Cooperative Principle in utterances produced by a person with ASD. The study shows that the participant mostly observes the four maxims indicated by providing truthful, sufficient, relevant and brief answers. Meanwhile, there are only two types of non-observance committed by the participant in this study, namely infringement and flouting. From the analysis, it is found that there are two factors that can cause a person with ASD to observe and not observe the maxims, namely his linguistic factors and his non linguistic factors